2020
DOI: 10.1249/mss.0000000000002421
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Perceived Exertion in People with Myalgic Encephalomyelitis/Chronic Fatigue Syndrome and Fibromyalgia: A Meta-analysis

Abstract: Purpose Myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS) and fibromyalgia (FM) are two debilitating illnesses primarily characterized by chronic symptoms of fatigue and musculoskeletal pain, respectively. Some investigators have observed an elevated sense of effort in these patient groups; however, this effect has not been substantiated via quantitative review. As such, we conducted a meta-analysis of RPE responses to aerobic exercise in ME/CFS and FM compared with healthy adults. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 77 publications
1
14
0
1
Order By: Relevance
“…Participants with ME/CFS rated exercise as requiring more effort throughout the test and these differences were maintained after matching for aerobic fitness. These results are consistent with a recent meta-analysis of 37 studies (involving 1016 with ME/CFS and 686 healthy controls) reporting large effect-size (d = 0.85) differences in RPE [65]. Based on the preponderance of data, it can be concluded that people with ME/CFS perceive exercise as requiring more effort than otherwise healthy people.…”
Section: Plos Onesupporting
confidence: 90%
“…Participants with ME/CFS rated exercise as requiring more effort throughout the test and these differences were maintained after matching for aerobic fitness. These results are consistent with a recent meta-analysis of 37 studies (involving 1016 with ME/CFS and 686 healthy controls) reporting large effect-size (d = 0.85) differences in RPE [65]. Based on the preponderance of data, it can be concluded that people with ME/CFS perceive exercise as requiring more effort than otherwise healthy people.…”
Section: Plos Onesupporting
confidence: 90%
“…In general people with CFS/ME perceive aerobic exercise as more effortful than healthy adults, this aspect is reflected in a meta-analysis but the exact causes are unclear [ 45 ]. The relevance of this effect requires further studies in order to elucidate the underlying mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…The perception of effort is involved in the regulation of human behavior [1] and influences how the nervous system selects a given movement amongst a myriad of possibilities [2, 3]. The perception of effort is altered in the presence of fatigue [4] and various pathologies such as chronic fatigue syndrome [5, 6], stroke [7] and cancer [8]. This perception is used to prescribe and monitor exercise in both rehabilitation programs [9, 10] and athletic training [11–13].…”
Section: Introductionmentioning
confidence: 99%